Digital morphogenic diagrammatic DIY lighting - Yusof, Wan Zaiyana; Puteri Fadzline, Muhamad Tamyez (2018)
This project is to work on innovative form which is to explore the subject of ‘supersurfaces’ which emphasizes of paper folding as a method of form generation. Associated with diagrammatic technique and digital morphogenesis,prolifically meterializing in the projected and the built through continuity, curvature,smooth layering and manupulations of the ground which was conceptualized Deleuzian ontology of the ‘the fold’. This project required to investigate paperfolds as physical artifacts to design a lighting.Folding and paper was used as a starting technique and material which involve the three-dimensional reproduction of, geometric patterns on various scales. The used of theory in knowledge building in reflective practice embedded with the theory of semantics showed that design-driven approach can be achieved for radical innovating of product design and development.